2023
DOI: 10.1002/ejlt.202200196
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐mediated plant oil hydrolysis—Toward a quantitative glycerol recovery for the synthesis of pure allyl alcohol and acrylonitrile

Abstract: Plant based triacylglycerides are a sustainable feedstock for the chemical, bioenergy, food and cosmetic sector. While fatty acids conversion has been intensively studied, processes for glycerol valorization have been scarce. In contrast to chemical hydrolysis of plant triacylglycerides enzymatic hydrolysis methods provide a cleaner glycerol stream. This study focuses on the selection of a commercial lipase capable of quantitative hydrolysis of rapeseed‐ and high oleic sunflower oils. Enzymatic process using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…For the first step of the cascade reaction, the commercially available lipase from Candida rugosa was used since it is known as a high-fidelity enzyme for the hydrolysis of triglycerides into free fatty acids and glycerol and is also active over a wide temperature and pH range [38,39]. Additionally, a recent screening experiment showed that Candida rugosa lipase was most efficient for rapeseed oil and HOSO conversion [40].…”
Section: A Cascade Reaction Using a Lipase And Ohyrementioning
confidence: 99%
“…For the first step of the cascade reaction, the commercially available lipase from Candida rugosa was used since it is known as a high-fidelity enzyme for the hydrolysis of triglycerides into free fatty acids and glycerol and is also active over a wide temperature and pH range [38,39]. Additionally, a recent screening experiment showed that Candida rugosa lipase was most efficient for rapeseed oil and HOSO conversion [40].…”
Section: A Cascade Reaction Using a Lipase And Ohyrementioning
confidence: 99%